2004
DOI: 10.4049/jimmunol.173.7.4627
|View full text |Cite
|
Sign up to set email alerts
|

Selective Impairment of TLR-Mediated Innate Immunity in Human Newborns: Neonatal Blood Plasma Reduces Monocyte TNF-α Induction by Bacterial Lipopeptides, Lipopolysaccharide, and Imiquimod, but Preserves the Response to R-848

Abstract: Newborns are at increased risk of overwhelming infection, yet the mechanisms underlying this susceptibility are incompletely defined. In this study we report a striking 1- to 3-log decrease in sensitivity of monocytes in human neonatal cord blood, compared with monocytes in adult peripheral blood, to the TNF-α-inducing effect of multiple TLR ligands, including bacterial lipopeptides (BLPs), LPS, and the imidazoquinoline compound, imiquimod. In marked contrast, TNF-α release in response to R-848, a TLR ligand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
331
8
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 341 publications
(376 citation statements)
references
References 28 publications
29
331
8
8
Order By: Relevance
“…TLR4 was expressed on a smaller subset of monocytes in preterm infants, but the expression was also equivalent across groups. Similar levels of mRNA and of protein expressions of TLR2 and TLR4 are reported in neonatal cells of term infants and in adult cells (35), whereas another study found that TLR4 expression increased with increasing GA (36). We conclude that differences in responses to SE in preterm infants are unlikely to result from GA-related increases in TLR2 expression.…”
Section: Monocyte Response To Staphylococcus Epidermidissupporting
confidence: 80%
“…TLR4 was expressed on a smaller subset of monocytes in preterm infants, but the expression was also equivalent across groups. Similar levels of mRNA and of protein expressions of TLR2 and TLR4 are reported in neonatal cells of term infants and in adult cells (35), whereas another study found that TLR4 expression increased with increasing GA (36). We conclude that differences in responses to SE in preterm infants are unlikely to result from GA-related increases in TLR2 expression.…”
Section: Monocyte Response To Staphylococcus Epidermidissupporting
confidence: 80%
“…The measure of responses on whole blood provides a more global determination of anti-microbial responses. Indeed, previous studies have demonstrated that neonatal plasma suppresses TLR-mediated cytokine production, indicating that both cellular and soluble humeral factors are important in the functional determination of immune responsiveness (13,14).Our data are consistent with previous studies that have measured a low surface expression of TLRs on blood mononuclear cells of preterm neonates, with TLR2 and TLR4 expression increasing during the first 2 mo of age (15). However, because TLR-dependent cytokine responses generally correlate poorly with their corresponding receptor gene or protein expression, it is important to validate the impact of a reduced expression of PRR at the functional level by examining relevant cytokine responses (6).…”
supporting
confidence: 83%
“…Based on published work (5,13,14), we usually tested cultures with R-848 at 1 g/ml to investigate its effects on HIV replication. Titrating R-848 from 10 -0.01 g/ml revealed a clear dose dependency: R-848 gradually lost its anti-HIV activity at concentrations Ͻ 0.1 g/ml (Fig.…”
Section: Dose-and Time-dependent Inhibition Of Hiv Replicationmentioning
confidence: 99%
“…The B cell line Namalwa was cultivated in RPMI 1640, 15% FCS, 1 mM sodium pyruvate, 1 mM nonessential amino acids, and 1% P/S. R-848 (InvivoGen) was used mainly at 1 g/ml (5,13,14), polyinosic: polycytidylic acid (poly(I:C); Amersham Biosciences) at 20 g/ml, flagellin from Salmonella typhimurium (provided by J. C. Sirard (Institut de Biologie de Lille, Université E0364 1, Lille, France)) at 100 g/ml, peptidoglycan from Staphylococcus aureus (Fluka) at 10 g/ml and LPS (Escherichia coli K-235; Sigma-Aldrich) at 20 g/ml. Sequences of phosphothioate-modified ssRNA (i.e., ssRNA40, 41, and 42) were identical to those published by Heil et al (6); in particular the RNA40 is a 20 mer identical to the U5 region from 108 to 127; RNA41 and 42 are 20 mer where all U or G nucleotides were replaced with adenosine, respectively (IBA).…”
Section: Cells Cell Lines and Reagentsmentioning
confidence: 99%